Analisis Jalinan Jalan (WEAVING AREA) pada Ruas Jalan Yos Soedarso-Kinibalu di Bundaran Besar Palangka Raya - Nirwana Puspasari; Ahmat Solikin (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The analysis was calculated based on the method of Indonesian Highway Capacity Manual 1997, which resulted in the form of volume, capacity, degree of saturation, delays and queues opportunities. Whereas the performance on the part of weaving area of daily traffic average at peak hours in the morning can actually capacity (C) = 3481.848 smp/h, the degree of saturation DS = 0.695, delay braided section (DT) = 3.799 sec/smp, and opportunities queue braided section (Qp%) = lower limit/minimum of 12.12%, and the upper limit/maximum of 28.18%. On the daily traffic average at peak hours during the day obtained the capacity actually (C) = 3495.967 smp/h, the degree of saturation DS = 0692, delay part of weaving area (DT) = 3,766 det/smp, and opportunities queue section weaving area (Qp%) = lower limit/minimum of 11.99%, and the upper limit/maximum of 27.89%. On the daily traffic, the average at peak hours in the afternoon, the accually capacity can be obtained (C) = 3593.639 smp/h, the degree of saturation DS = 0673, delay part weaving area (DT) = 3,546 det/smp, and opportunities queue section weaving area (Qp %) = lower limit/minimum 11.16%, and the upper limit/maximum of 25.95%. Based on the analysis, the results obtained Degree of Saturation (DS) to all parts of weaving area is less than 0.75 the terms set forth in MKJI, 1997 so that each hour of the peak that occurred in parts of weaving area on Yos Sudarso-Kinibalu street is still qualify.